2022
DOI: 10.3390/s22041487
|View full text |Cite
|
Sign up to set email alerts
|

A Software Defined Radio Based Anti-UAV Mobile System with Jamming and Spoofing Capabilities

Abstract: The number of incidents between unmanned aerial vehicles (UAVs) and aircrafts at airports and airfields has been increasing over the last years. To address the problem, in this paper we describe a portable system capable of protecting areas against unauthorized UAVs, which is based on the use of low-cost SDR (software defined radio) platforms. The proposed anti-UAV system supports target localization and integrates effective jamming techniques with the generation of global positioning system (GPS) spoofing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…In addition to technical parameters, it is also worth mentioning the functional parameters of anti-drone systems, such as software-defined functionality or sensory multi-functionality. The software-defined functionality enables additional functions of the anti-drone system, such as automatic self-calibration, dynamic detection and frequency allocation, dynamic disturbance detection, the automatic launch of anti-disturbance modes, remote system operation and configuration and software updates [12]. The sensory multi-functionality of anti-drone systems is based on the application of multisensory sensor fusion (radar, optical, thermal imaging) enabling the detection and tracking of various types of objects, i.e., drones, people and vehicles in full azimuth and hemispheric coverage, and feature extraction for the classification process of detected objects [13].…”
Section: Review Of Anti-drone Systemsmentioning
confidence: 99%
“…In addition to technical parameters, it is also worth mentioning the functional parameters of anti-drone systems, such as software-defined functionality or sensory multi-functionality. The software-defined functionality enables additional functions of the anti-drone system, such as automatic self-calibration, dynamic detection and frequency allocation, dynamic disturbance detection, the automatic launch of anti-disturbance modes, remote system operation and configuration and software updates [12]. The sensory multi-functionality of anti-drone systems is based on the application of multisensory sensor fusion (radar, optical, thermal imaging) enabling the detection and tracking of various types of objects, i.e., drones, people and vehicles in full azimuth and hemispheric coverage, and feature extraction for the classification process of detected objects [13].…”
Section: Review Of Anti-drone Systemsmentioning
confidence: 99%
“…The GPS protocol is vulnerable to spoofing attacks, since it lacks encryption and authentication mechanisms. As a result, attackers can inject false GPS signals using software-defined radio (SDR) [ 7 ] or dedicated GPS spoofers (which can be purchased online), causing the drone to believe that it is flying in a location that differs from the actual location. Studies have shown that GPS spoofing attacks against drones can cause a drone flying in autonomous mode to accelerate in the attacker’s chosen direction [ 8 ] (by transmitting fake GPS coordinates in the opposite direction); force a drone flying in manual mode to land [ 9 ] (by sending a no-flight zone alert that triggers a safety mechanism, causing the drone to land); or change the direction of the drone’s movement itself [ 10 ].…”
Section: Related Workmentioning
confidence: 99%
“…Para el presente año (Powell et al, 2022) realizó una investigación sobre la gestión de la movilidad de los UAV mediante el uso de SDR para el diseño metodológico de prueba, con la finalidad de la construcción de un prototipo. Finalmente (Ferreira et al, 2022), en su artículo denominado "Un sistema móvil anti-UAV basado en radio definido por software con capacidades de interferencia y suplantación de identidad", planteó la idea de poder usar SDR de bajo costo para la implementación en sistemas anti UAV. Como se evidencia, el uso de la SDR es diverso y muy eficiente en los diferentes tipos de aplicaciones; así mismo, se demuestra que existe una industria especializada para el desarrollo de estos prototipos.…”
Section: Perspectivas En Inteligenciaunclassified